Novel idebenone derivatives attenuated oxidative stress injury and myocardial damage - Peng, Yuwei; Guo, Yishan; Yang, Xinyi; Liu, Yulan; Xu, Xun; Chen, Junhong; Liu, Xueyi; Xie, Zhenrou; Yu, Zhiqiang; Wu, Dudu; Chen, Zhi (Frontiers in Chemistry, 2025)
Oxidative stress-induced cardiomyocyte apoptosis was the primary causative factor of cardiovascular disease (CVD). However, the existing therapy drugs for oxidative stress were much less investigated, which underlined the necessity for new drug discovery and development. Herein, we aimed to synthesize several novel idebenone (IDE) derivatives and investigate the protective effect and mechanism of these derivatives against H2O2-induced oxidative stress injury in H9C2 cells by determining cell proliferation rate, detecting the reactive oxygen species (ROS) level, and the expression of related proteins. Additionally, the study also investigated the protective effect of IDE-1 pretreatment on Balb/c mice after hypoxia-reoxygenation. In vivo experiments, the damage to cardiomyocytes was assessed using hematoxylin-eosin (HE) staining and terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) staining. The results showed that IDE-1 possessed the highest antioxidant damage activity among all IDE derivatives, which could notably decrease the levels of intracellular ROS. Furthermore, the antioxidant mechanism was confirmed to be potentially linked to the expression levels of the oxidation-related pathway heme oxygenase-1 (HO-1) and the apoptosis-related pathway Bcl-2/Bax and caspase-3. Our results demonstrated that IDE derivatives could be a new research direction for the treatment of cardiovascular diseases associated with oxidative stress.